Two new ‘incertae sedis’ syllids (Annelida: Syllidae) from Brazilian oceanic islands - Nascimento, Rodolfo Leandro; Fukuda, Marcelo Veronesi; Paiva, Paulo Cesar de (European Journal of Taxonomy, 2024)
Oceanic islands harbor a unique and distinct fauna and flora, usually isolated by distance and the deep sea, making them fascinating environments to study. Despite their importance, taxonomic accounts from Brazilian oceanic islands have only recently begun to focus on important groups such as the Syllidae family. In this article, we present detailed descriptions and illustrations of two new species, Brevicirrosyllis paulolanai sp. nov. from Trindade Islands, and Westheidesyllis splendida sp. nov. from Rocas Atoll. These two species belong to genera currently of uncertain affinities within the family, in both cases previously included in the Eusyllinae subfamily. Moreover, we provide updated identification keys for both genera to facilitate their future identification.